Analysis of motives, context and bidirectionality of dating violence in young couples - Rojas-Solís, José Luis; Romero-Méndez, Christian Alexis (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2023)
The possible bi-directionality of violence in young couples is a heavily debated topic in the scientific literature, which is why it requires greater specification in its analysis. This study is aimed at identifying the motives, context and response to dating violence behavior using a quantitative approach. A sample of 539 Mexican adolescents was used with a profile of victims and perpetrators. The results indicated jealousy as being the main motive why different forms of dating violence are committed and suffered, as well as noting that most of these violent acts usually arise in the middle of an argument. Furthermore, a similar percentage of men and women could use violence as a form of self-defense to other forms of violence exerted by their partner. In conclusion, more studies are needed to analyze the motives and context of violent acts and determine whether mutual violence arises as a form of self-defense or as a way to gain power and control over the other party.